ENUMERATION OF LICHEN BIOTA FROM DAVANGERE DISTRICT OF KARNATAKA - SHWETHA ULLEGADDI; VINAYAKA K.S; SANJEEVA NAYAKA; ANKITHA S; DEEPAK GOWDA H S; MADHU KUMAR DJ; SHWETA G M; MANASA D.J (The Bioscan, 2025)
Lichens, which are symbiotic relationships association between cyanobacteria or algae and fungi and are considered as bio-indicators of the environment health. Lichen diversity is still poorly understood in many regions of India, including Karnataka's Davanagere district, despite its ecological importance. The aim of this study is to record the diversity of lichens found in Davanagere district with distinct habitats. We identified 26 lichen species from 16 genera and 8 families through methodical field surveys carried out in forest, semi-forested, agriculture, urban and rural areas. Crustose and fruticose lichens were the next most common growth forms, after foliose lichens. Dirinaria, Graphis, Lecanora, Parmotrema, Physcia, Pyxine and Ramalina are the most commonly available genera. The results establish a baseline for upcoming ecological and environmental monitoring research and offer fresh perspectives on the lichen biota of central Karnataka.